Neuroprotective Effects of Oligosaccharides in Rehmanniae Radix on Transgenic Caenorhabditis elegans Models for Alzheimer’s Disease - Kang, Nianxin; Luan, Yage; Jiang, Yu; Cheng, Wenhao; Liu, Yongjian; Su, Zhijun; Liu, Yonggang; Tan, Peng (Frontiers in Pharmacology, 2022)
Rehmanniae Radix (RR, Rehmannia glutinosa (Gaertn.) DC.) is an important traditional Chinese medicine distributed in Henan, Hebei, Inner Mongolia and Northeast in China. RR is frequently used to treat diabetes mellitus, cardiovascular disease, osteoporosis and aging-related diseases in a class of prescriptions. The oligosaccharides and catalpol in RR have been confirmed to have neuroprotective effects. But there are few studies on the anti-Alzheimer's disease (AD) effect of oligosaccharides in Rehmanniae Radix (ORR) is. The chemical components and pharmacological effects of dried Rehmannia Radix (DRR) and prepared Rehmannia Radix (PRR) are different because of the different processing methods. ORR has neuroprotective potential, such as improving learning and memory in rats. Therefore, the aim of this study was to prove the importance of oligosaccharides in DRR (ODRR) and PRR (OPRR) for AD based on the Caenorhabditis elegans (C. elegans) model and the different roles of ODRR and OPRR in the treatment of AD. In this study, we used paralysis assays, lifespan and stress resistance assays, bacterial growth curve, developmental and behavioral parameters and ability of learning and memory to explore the effects of ODRR and OPRR on anti-AD and anti-aging. Furthermore, the accumulation of reactive oxygen species (ROS), deposition of Aβ and expression of amy-1, sir-2.1, daf-16, sod-3, skn-1 and hsp-16.2 were analyzed to confirm the efficacy of ODRR and OPRR. OPRR was more effective than ODRR in delaying the paralysis, improving learning ability and prolonging lifespan of C.elegans. Further mechanism studies showed that the accumulation of ROS, the aggregation and toxicity of Aβ were reduced, suggesting that ORR alleviated Aβ-induced toxicity, in part, through antioxidant activity and Aβ aggregation inhibiting.The expression of amy-1 was down-regulated, sir-2.1, daf-16, sod-3 and hsp-16.2 were up-regulated. Thus, ORR could have a possible therapeutic effect for AD by modulating the expression of amy-1, sir-2.1 daf-16, sod-3 and hsp-16.2. Furthermore, ORR promoted the nuclear localization of daf-16, and further increased the expression of sod-3 and hsp-16.2, which made a significant contribution to inhibite the Aβ toxicity and enhance oxidative stress resistance. In summary, the study provided a new idea for the development of ORR.